Kesantunan dalam Pujian atas Kemampuan di Kolom Komentar Yahoo News Japan: Kajian Cyberpragmatics - Prastika, Tiara Maulina; Sunarni, Nani; Kadir, Puspa Mirani (KIRYOKU, 2025)
This study aims to describe the politeness strategies in the form of ability compliments used by Japanese netizens in the comments column of Yahoo News Japan about the missing scissors incident at New Chitose Airport, Hokkaido. The research method used is descriptive qualitative with data taken from comments published on August 19–20, 2024. The object of research is comments that contain compliments on abilities, correct actions, or commendable behavior. Data analysis used the classification of compliments by Mizutani & Mizutani (1987), the politeness strategies of Brown & Levinson (1987), and the concept of cyberpragmatics from Rahardi (2020). From the analysis, it was found that all compliments use the positive politeness strategy. The compliments appear in several forms, such as explicit praise for discipline, recognition of correct responses, and empathetic expressions that emphasize solidarity. This shows that even though the comments were written anonymously, Japanese netizens still uphold politeness values such as enryo (modesty) and wakimae (social conformity). In the context of cyberpragmatics, compliments not only function as positive evaluations but also as a way to strengthen relationships, give moral support, and maintain collective identity (wa/和) in digital communication.